Synthesis, photophysical characterization, and DSSC application of 3,6-carbazole-based incorporating fused dipyrrolo-phenazine substitution as novel auxiliary donors - Hasan, Hiba Ali; Abd Alrazzak, Nour; Abdulrada, Nawar Jamal; Mohammed, Mohammed Ahmed; Mashyakhi, Tahani; Mahmoud, Hassab Alla M.A.; Abdulkareem-Alsultan, G.; Abdulmalek, Emilia; Nassar, Maadh Fawzi (Elsevier B.V., 2026)
Three dyes, DPP-CAR, DPPT-CAR, and DPPF-CAR were designed and synthesized based on a 3,6-C₂V-shaped carbazole (CAR) donor system incorporating fused dipyrrolo-phenazine (DPP) units as auxiliary donors and cyano acrylic acid (CAA) as the acceptor unit. The tailoring DPP-CAR dye follows a (D)2-D-π-A framework, whereas (D-π)2-D-π-A was utilized for DPPT-CAR and DPPF-CAR, with thiophene and furan units as π-bridges, respectively. Through comprehensive spectroscopic studies such as 1H, 13C. NMR, mass spectrometry and elemental analysis, the molecular structures were confirmed. The impact of DPP, DPPT, and DPPF moieties on optical properties, energy levels, and structural characteristics of the 3,6-substituted carbazole was rigorously evaluated by applying density functional theory (DFT) and time-dependent density functional theory (TD-DFT) methodologies. Their photophysical properties revealed a good Ultraviolet–visible spectrophotometry (UV–Vis) absorption enhancement range of 480–508 nm compared to the reference (401 nm), which can be attributed to the strong intermolecular charge transfer (ICT) between the proposed donor and acceptor. Finally, the DSSC devices were manufactured utilizing DPP-CAR, DPPT-CAR, and DPPF-CAR-based sensitizers, TiO₂-based photoanodes, and electrolyte respectively, to achieve considerable power conversion efficiencies (PCE) of 5.59, 7.57, and 6.14 % respectively. Additionally, the charge regeneration and recombination resistances (Rrec) along with electron lifetime (τeff) were measured by utilizing electrochemical impedance spectroscopy (EIS). As a result of the dye anti-aggregation caused by the DPPT fragment, DPPT-CAR demonstrated higher τeff (27.74 ms) and Rrec (56.54 Ω) compared to the rest of the dyes. As such, this study establishes that the proposed 3,6-DPP, DPPT, DPPF substitutions significantly improves the performance and efficiency of dye-sensitized solar cells (DSSCs).